Pediatric Conditions Requiring Minimal Intervention or Observation After Interfacility Transfer. Issue 7 (16th June 2021) - McDaniel, Corrie E; Leyenaar, JoAnna; Sullivan, Erin; Desai, Sanyukta; Kessler, Larry
Abstract : Increasing regionalization of pediatric care has led to interfacility transfer of children with general pediatric conditions at rates similar to those of high‐risk adults, which may delay appropriate treatment. We sought to identify common medical diagnoses that did not require significant advanced intervention and that had high rates of discharge within 1 day of interfacility transfer. Using the Pediatric Health Information System (PHIS) database, we identified all transfers into PHIS‐participating children's hospitals in 2019. We excluded encounters for mental health, labor/maternity, primary newborn diagnoses, and direct admissions to an intensive care unit. Eligible encounters were categorized by duration of hospitalization and basic vs advanced intervention after transfer. Of 286, 905 transfers, 197, 386 (68.6%) met inclusion criteria. Cough, febrile seizures, croup, and allergic reactions required advanced interventions <10% of the time, and patients with these diagnoses were most commonly discharged within 1 day after transfer. These conditions are potential targets for building pediatric capacity in non‐pediatric hospitals. Abstract :